A Study on Area Ease Distribution between Body and Garment (Journal of Fiber Bioengineering and Informatics, 2009)
Using 3D scan data, the ease-space area relations between a standard body and a specific style of garment with various sizes are studied. The least square method, cubic polynomial approximation and even arc-length with the idea of reverse engineering are employed in analyzing the curves of different cross sections of the body and the garment. Moreover, the area between the body surface and the garment section curves is used in calculating the ease-space distribution along with the changes of the body angles. 30% of the total ease space is distributed in the front and back and 70% around the sides and waist if the garment is to possess a good appearance, which is provided in an evaluation indicator used for the 3D garment simulation. This study is useful in further investigation of the fitness of garments on the human body, and it provides an evaluating indicator in the 3D garment simulation. It can also be used in firefighting industry for the air gap calculation and fireproof clothing.
Keywords: 3D scanning; curve fitting; area ease; distribution relation